Letras misivas, letras humanas, letras divinas. La correspondencia del cardenal Granvela en la Real Biblioteca y sus cartas de autores - Moreno Gallego, Valentín (Cuadernos de Historia Moderna, 2006)
The collection of letters by Cardinal Granvela in the Royal Library, with letters to Antoine Perrenot and memorandum of the burgundian, are an invaluable resource for scholars of Habsburg’s Monarchy in the 16th century. The collection sheds light on a wide range of subjects, from the mechanisms of governement and military geopolitics, to court intrigues and european artistic life. Following a brief introduction that looks at the importance of letter-writing as means of exercising political power in the 16th century, the present article advances a theory about the provenance of the collection based on a close reading of the letters and focuses on its impact on written culture by a brief commentary of the author’s letters.